2007
DOI: 10.1016/j.devcel.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Time of Exposure to BMP Signals Plays a Key Role in the Specification of the Olfactory and Lens Placodes Ex Vivo

Abstract: Spatial gradients of extracellular signals are implicated in the patterning of many different tissues. Much less is known, however, about how differences in time of exposure of progenitor cells to patterning signals can influence different cell fates. Bone morphogenetic protein (BMP) signals are known to pattern embryonic ectoderm. The olfactory and lens placodes are ectodermal structures of the vertebrate head. By using an explant assay of placodal cell differentiation, we now provide evidence that BMP signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
176
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(191 citation statements)
references
References 34 publications
14
176
1
Order By: Relevance
“…Fate and specification maps have shown that at neural fold stages, olfactory and lens placodal progenitor cells are spatially separated (figure 2b) [10,19,24]. This process strongly resembles the development of the eye and the odour-detecting antenna in Drosophila, where the visual and olfactory cells arise from a common imaginal disc, and at later stages separate and acquire their distinct identities [25].…”
Section: Directed or Random Migrationmentioning
confidence: 95%
See 4 more Smart Citations
“…Fate and specification maps have shown that at neural fold stages, olfactory and lens placodal progenitor cells are spatially separated (figure 2b) [10,19,24]. This process strongly resembles the development of the eye and the odour-detecting antenna in Drosophila, where the visual and olfactory cells arise from a common imaginal disc, and at later stages separate and acquire their distinct identities [25].…”
Section: Directed or Random Migrationmentioning
confidence: 95%
“…However, at this stage independent of rostrocaudal position, prospective neural plate border cells are specified as neural crest cells, but no placodal cells are detected [12], indicating that at the late blastula stage lens cells are not yet specified. Shortly thereafter, at the late gastrula stage, rostral neural plate border explants cultured in vitro generate cells of lens character, providing evidence that the initial specification of lens cells occurs at the late gastrula stage [19]. In contrast, in Xenopus embryos, lens cells are suggested to be specified as the neural tube closes [20], which can be due to differences in experimental settings or a species-specific difference.…”
Section: Lens Cells Are Initially Specified At Gastrula Stagesmentioning
confidence: 99%
See 3 more Smart Citations